Persuasive Communication And Work Effectiveness Enhancing Performance Of Employees In DPRD Merangin Regency - Supriyati; Misra Yeni; Ira Yumita; Darham (Journal of Economics, Business, and Government Challenges, 2020)
Persuasive communication and good work effectiveness could enhance employee performance. The purpose of this studied to determine and analyze variables of the persuasive communication and work effectiveness that affect the performance of the DPRD office staff Merangin Regency. This survey used the survey sampling of 45 office staff with multiple Linear Regression. The results that partially and simultaneously showed the influence of persuasive communication and work effectiveness variables on employee performance and the persuasive communication variables had more enhancing than work effectiveness variables. The value of R is 0.754 or 75.4% further research can examine qualitative methods or mixed methods or can use other variables so that employee performance can continue to be improved.